Trends in Air Pollution in Ireland: A Decomposition Analysis - TOL, RICHARD S. J. (ESRI)
Trends in the emissions to air of sulphur dioxide, nitrogen oxides, carbon monoxide, volatile organic compounds, and ammonia in Ireland are analysed with a logarithmic mean Divisia index decomposition for the period of 1990-2009. Emissions fell for four of the five pollutants, with ammonia being stationary, despite rapid economic change. A fall in emissions per unit output was the main driver of this trend, except for ammonia where structural economic change was the main driver. Extrapolating these trends continue, Ireland will keep emissions below its National Emission Ceilings, except in the case of nitrogen oxides where the target will likely be met by 2015.
PUBLISHED
Keywords: decomposition analysis; Ireland; emissions; air pollutants